Dataset "AR SUS & QUIS Hololens" - Li, Wen-Chin; Zhang, Jingyi; Blundell, James; Court, Samuel (Cranfield University, 2024)
AR system usability and user experience in flight operations
Keywords: augmented reality; multimodal interaction; single pilot operations; system usability; user interface experience